CARDIOPROTECTIVE ACTIVITY ASSOCIATED WITH THE USE OF THE GUAZUMA ULMIFOLIA LAM. AN INTEGRATIVE REVIEW OF THE LITERATURE - Chiacchio, Adolpho Dias; Costa, Alice Freitas; Ramos, Giovana Lis Galvão; de Siqueira, Sarah Brito; Fonseca, Juliana Barros; Silva, Lucas Martins; Spíndola , Giovana Antunes; de Bessa, Manuela Faria (ARACÊ, 2024)
Comorbidities, particularly those related to the cardiovascular system, are prevalent in today's lifestyle, contributing significantly to morbidity and mortality rates according to the World Health Organization. Obesity and sedentary habits further exacerbate cardiovascular risks, often demanding multidrug therapies. Herbal medicine offers popular alternatives to reduce drug reliance, with plants like Guazuma ulmifolia playing a significant role due to its geographical prevalence and the presence of beneficial compounds such as proanthocyanidins, epicatechins, and flavonoids. This review aims to highlight G. ulmifolia's positive impact on cardiovascular health based on existing evidence. An integrative literature review was conducted using SCOPUS, PUBMED, and WEB OF SCIENCE databases with specified descriptors like "Phytotherapy", "Guazuma ulmifolia" and "Mutamba". Studies indicate that G. ulmifolia exhibits anti-inflammatory, hypoglycemic, vasodilatory, antioxidant, and cardiotonic properties attributed to its phenolic compounds. Ultimately, the cardioprotective potential of G. ulmifolia suggests its promising role as an adjunct therapy alongside conventional treatments, although further research is warranted to enhance the understanding of its therapeutic mechanisms.